Identifikasi Molekuler Hawar Daun Bakteri (Xanthomonas oryzae pv. oryzae) dan Uji Patogenisitasnya pada Galur-galur Padi Isogenik - Tasliah Tasliah; Mahrup Mahrup; Joko Prasetiyono (Jurnal AgroBiogen, 2013)
Identification of Xanthomonas oryzae pv.oryzae (Xoo) based on molecular analysis has beenintroduced just few years ago. This method used somespecific primers for Xoo and can be done quickly. Thepurposes of this research were to identify isolate Xoooriginated from five locations in Indonesia and to determinethe level of pathogenicity of these bacteria. Studies wereconducted in the greenhouse and the Molecular BiologyLaboratory of ICABIOGRAD, from 2011 to 2012. Bacterialisolates were taken from five regions in Indonesia, namely:West Sumatra, West Java, Central Java, South Sulawesi, andWest Kalimantan. The specific primers of Xoo wereXoo2967, Xoo80, and Xoo. Results showed that 216 isolatescould be grown to form yellow colored colonies, whichbelongs to a criterian for Xoo. Molecular analysisdemonstrated that 189 isolates were Xoo and 27 isolateswere not. Amplification of DNA of the isolates resulted a 337bp PCR product for primer Xoo2976, 700 bp for primerXoo80 and 534 bp for primer Xoo. Pathogenicity tests of theXoo isolates showed xa5, Xa7, and Xa21 resistance geneswere still effective againts BLB pathogens originated fromthose five regions, with percentage of resistance were 93.57,77.49, and 85.37%, respectively.